Replication of a skills assessment for auditory–visual conditional discrimination training. Issue 2 (22nd February 2022) - Kodak, Tiffany; Bergmann, Samantha; Cordeiro, Maria Clara; Bamond, Meredith; Isenhower, Robert W.; Fiske, Kate E.
Abstract : Auditory–visual conditional discrimination training (e.g., receptive identification training, listener responses; AVCD) is ubiquitous in early intervention and special education programs. Nevertheless, some learners with Autism Spectrum Disorder (ASD) do not appear to benefit from this training despite use of empirically validated treatments. To prevent exposure to extended training that does not lead to learning, a skills assessment that measures skills related to AVCD training will be useful for educators and practitioners. The current study replicated the skills assessment developed and evaluated by Kodak et al. (2015) with 8 participants with ASD who received behavior analytic intervention that included at least 1 goal related to AVCD training. Two of the 8 participants mastered all skills included in the assessment except scanning. In addition, 5 participants' responding failed to reach mastery during subsequent exposure to AVCD training, which further demonstrated the predictive utility of the skills assessment.